INFILTRATION WELLS ALTERNATIVES TO REDUCE WATER PUDDLE IN LOWOKWARU DISTRICT, MALANG CITY - Hirijanto, Hirijanto; Mundra, I Wayan; Wedyantadji, Bambang (Journal of Sustainable Technology and Applied Science (JSTAS), 2021)
Surface waters give a plentiful supply of waters ready to be utilized for residence, farmland, fishery, industry, and electric generating machine, and most importantly, to deal with the problem of water scarcity (crisis). Rain is one of the hydrological cycles that help to preserve groundwater (shallow groundwater). During the rainy season, most waters go directly to the river and the sea without processing, creating inundations and flood in some places. Water resources, however, begin to lose their supporting capacity. Water supply is no longer balanced with the demand that starts to bulge up excessively. This disrupted balance is indicated by many critical lands that are less productive and incapable of absorbing waters to the ground. Considering this outline, the implementation of environmentally friendly infiltration wells can be a strategic option to solve the water balance issue. Some alternatives of infiltration wells are proposed as the solution to the problem that this research deals with. It is estimated that these wells can reduce 10%-15% of surface runoff rate in Lowokwaru District of Malang City, especially around Soekarno-Hatta Street that always leaves massive water puddle, especially during the rainy season. This research gives the relevant institutions and user community information about drainage construction, drainage network, and land use above drainage network. Through this information, it is expected that the follow-up can be given efficiently to produce an optimum and effective drainage network. Community participation, therefore, is needed to maintain the benefits of alternative infiltration wells to ensure their sustainability in the future.